Awomansplace: Let’s have a constructive conversation - Zonneveld, Makheni (Bookboon, 2020)
This book is part of Project awomansplace. The objective is to have an online conversation on the kind of society we want our children and their children to inherit. The focus is on how we can remake our society by remaking the workplace.